Sosiologi Kritis Teori Sosiologi Michel Foucault - A Safriadi Darmansyah A; Arlin Arlin; Syamsu A Kamaruddin (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
Foucault is highly interested in examining how knowledge and power interact. There is no power exercise that does not result in knowledge, and there is no knowledge that does not take into account power interactions. Modern people are born as the objects and subjects of power nets that distribute and provide for them, according to Foucault. One of the most amazing philosophers is Michel Foucault. His capacity for thought is limitless. His ideas have influenced everything from history, philosophy, social and political sciences, to the medical industry, which his family works in. Because the conclusions of his thinking ran counter to the prevailing modernist theories of the period, Foucault is frequently referred to as a post-modernist, post-structuralist, or even a philosopher. However, he rejected all of these labels. Foucault's interest in themes of humanity, marginality, abnormality, and his conception of truth are key strengths of his ideas. This essay covers Foucault's core ideas on knowledge, power, discipline, and law. Keywords: Discipline, Knowledge, Law, Power